2021
DOI: 10.1007/s40471-021-00267-4
|View full text |Cite
|
Sign up to set email alerts
|

Aging and COVID-19 in Minority Populations: a Perfect Storm

Abstract: Purpose of Review COVID-19 is a major concern for the health and wellbeing of individuals worldwide. As COVID-19 cases and deaths continue to increase in the USA, aging Black and Hispanic populations have emerged as especially at-risk for increased exposure to COVID-19 and susceptibility to severe health outcomes. The current review discusses the weathering hypothesis and the influence of social inequality on the identified health disparities. Recent Findings Aging mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…In addition to current inequalities, United States perspectives emphasized that historic events influence vulnerabilities ( Krishnan et al, 2020 ; Garcia, 2021 ) regardless of elapsed time. For example, United States-based commentaries pointed out that racism toward BIPOC patients deteriorates trust in the health care system ( Walubita et al, 2021 ); recounts of the 1918 influenza pandemic reveal neglect and erasure of BIPOC in documentation of diseases and civic and healthcare participation. Consequently, disparities in health are sustained, emphasizing the need to collect diverse health data that go beyond the “norm” individual as critiqued in a United States article ( Krishnan et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to current inequalities, United States perspectives emphasized that historic events influence vulnerabilities ( Krishnan et al, 2020 ; Garcia, 2021 ) regardless of elapsed time. For example, United States-based commentaries pointed out that racism toward BIPOC patients deteriorates trust in the health care system ( Walubita et al, 2021 ); recounts of the 1918 influenza pandemic reveal neglect and erasure of BIPOC in documentation of diseases and civic and healthcare participation. Consequently, disparities in health are sustained, emphasizing the need to collect diverse health data that go beyond the “norm” individual as critiqued in a United States article ( Krishnan et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since the outbreak of the coronavirus disease, minority and marginalized older adults have faced greater risk of COVID-19 exposure, infection, and complications, in large part because of the daily realities of historical and ongoing oppression and social injustice ( Walubita et al, 2021 ). A growing number of studies have also demonstrated that the pandemic has had far-reaching consequences beyond the physical effects of the disease itself.…”
Section: Discussionmentioning
confidence: 99%
“…These adverse health outcomes are well documented by physical health researchers and include, but are not limited to, increased rates of hypertension, cardiovascular disease, kidney disease, and diabetes (Ferdinand et al, 2017;Simons et al, 2021). More recently, researchers have documented the weathering hypothesis as an explanation for increased rates of exposure and serious complications as they relate to older BIPOC individuals and COVID-19 (Bhatt, 2021;Walubita et al, 2021). The weathering hypothesis offers an explanation for both the physical impacts that a lifetime of adversity has on the body and the mental health vulnerabilities BIPOC individuals experience due to exposure to traumatic incidents across their life span (Iyanda & Lu, 2021).…”
Section: Trauma Across the Life Span And Generationsmentioning
confidence: 99%
“…Although the prevalence rate of psychological distress in older African Americans is higher than that of their White peers, they are significantly less likely to seek out mental health care (Cook et al, 2019;Jimenez et al, 2013). The aftermath of the COVID-19 pandemic highlights the long-standing disparity in accessing adequate health care for older African American, Hispanic, and Indigenous individuals as they are at higher risk for long-term complications and death (Walubita et al, 2021). Chatters et al (2020) referred to this as "double jeopardy," defined as the "impacts of racism and ageism and race-and age-based discrimination" (p. 855).…”
Section: Trauma Across the Life Span And Generationsmentioning
confidence: 99%
See 1 more Smart Citation